Investigation for conductor loss calculation including effect of adhesive layer of titanium in microwave, millimetre and terahertz frequency range. (2022) - Bansal, Ritu; Kumar Mishra, Sanjay; Kumar, Yogesh; Uke, Santosh J.; Mardikar, Satish P.; Pandit, Vikram U.
Abstract: This paper presents the investigation of calculations for conductor loss including effect of adhesive layer of Ttitanium from frequency range 1 GHz to 1000 GHz. Here we present comparison between experimental conductor loss of the Thin Film Microstrip line with loss calculation from suggested model for the structures of TFML. It is found that the loss estimation in Millimeter wave and Terahertz frequency range is much more with adhesive layer than without adhesive layer in comparison to Microwave range for Thin Film Microstrip Line.